The recent decline in employment dynamics - Henry R. Hyatt; James R. Spletzer (IZA Journal of Labor Economics, 2013)
We document and attempt to explain the recent decline in employment dynamics in the U.S. We have four major empirical findings. First, each measure exhibits a 'stair step' pattern, with the declines concentrated in recessions and little increase during subsequent expansions. Second, changes in the composition of workers and businesses can explain only a small amount of the decline. Third, any explanation for the decline in job creation and job destruction will account for no more than one-third of the decline in hires and separations. Fourth, the decline in hires and separations is driven by the disappearance of short-duration jobs.
Keywords: E24; J63; 330; Hires; Separations; Job creation; Job destruction; Job-to-job flows